Membrane lipids and their degradation compounds control GM2 catabolism at intralysosomal luminal vesicles - Anheuser, Susi (J Lipid Res, 2019)
The catabolism of ganglioside GM2 is dependent on three gene products. Mutations in any of these genes result in a different type of GM2 gangliosidosis (Tay-Sachs disease, Sandhoff disease, and the B1 and AB variants of GM2 gangliosidosis), with GM2 as the major lysosomal storage compound. GM2 is also a secondary storage compound in lysosomal storage diseases such as Niemann-Pick disease types A–C, with primary storage of SM in type A and cholesterol in types B and C, respectively. The reconstitution of GM2 catabolism at liposomal surfaces carrying GM2 revealed that incorporating lipids into the GM2-carrying membrane such as cholesterol, SM, sphingosine, and sphinganine inhibits GM2 hydrolysis by β-hexosaminidase A assisted by GM2 activator protein, while anionic lipids, ceramide, fatty acids, lysophosphatidylcholine, and diacylglycerol stimulate GM2 catabolism. In contrast, the hydrolysis of the synthetic, water-soluble substrate 4-methylumbelliferyl-6-sulfo-2-acetamido-2-deoxy-β-d-glucopyranoside was neither significantly affected by membrane lipids such as ceramide or SM nor stimulated by anionic lipids such as bis(monoacylglycero)phosphate added as liposomes, detergent micelles, or lipid aggregates. Moreover, hydrolysis-inhibiting lipids also had an inhibiting effect on the solubilization and mobilization of membrane-bound lipids by the GM2 activator protein, while the stimulating lipids enhanced lipid mobilization.—